Distribution and Description of Indigofera trita L.F. Spp. Subulata (Vahl Ex Poir) Ali - A Rare Plant in the Kolli Hill of Tamil Nadu - Ramachandran, A.; Soosairaj, S.; Jayakumar, S. (Indian Forester, 2006)
No abstract